Bilingualism Practices on Cinta Laura and Daniel Mananta’s Podcast - Azzahra Happy Tivani (JALL (Journal of Applied Linguistics and Literacy), 2026)
This study examines how Cinta Laura and Daniel Mananta, two well-known Indonesian public figures who often speak in English and Indonesian, use both languages in their podcast conversations.  This research analyzes one selected podcast episode to determine the classification of coordinative, subordinative, and compound bilingualism based on Weinreich's classification. A descriptive qualitative approach was used in this study. After data was collected through listening and note-taking, categorization and frequency analysis of bilingual utterances were conducted.  The results show that compound bilingualism is the most common (48 percent), indicating that both languages are integrated into a single, unified system of meaning.  Subordinate bilingualism is very common (36 percent), where Indonesian is used as the basis for thinking while English is used for emphasis or stylistic effect. Most cases of coordinative bilingualism (16%) occurred when speakers used English exclusively without relying on Indonesian.  These results indicate that young Indonesian speakers use bilingualism flexibly and strategically in digital media, with Indonesian remaining the basis of communication while English adds expressiveness, a modern feel, and global appeal. This study enhances our understanding of bilingual practices in informal digital discourse and encourages further research on bilingualism across different speaker backgrounds and media formats.